(untitled) (Research, Society and Development, 2020)
The present research aims to evaluate the effect of treatment for low back pain using motion sensors, by analyzing the level of pain, verifying the range of motion (ROM) of the spine, and the degree of physical disability in the pre and post treatment. Patients underwent pre- and post-treatment assessment using the Numerical Verbal Scale to measure pain level, stabilometry to assess stability, Roland-Morris Disability questionnaire for level of functionality and goniometry to measure Range of Motion. In treatment, one session per day was carried out for 10 consecutive days, each session lasting 30 minutes. The results demonstrate that there was a decrease in the level of pain in the patients (P = 0.0008). In addition, the level of functionality also decreased significantly (P = 0.001) and a slight increase in goniometric values. Through the results obtained, it is concluded that the use of Wearable in patients with low back pain proves to be effective in the treatment of the disease, allowing for pain relief, increased range of motion and improved functional capacity of patients.